STRATEGI PERANCANGAN SEKOLAH ALAM SMK PERTANIAN DENGAN PENDEKATAN SISTEM PERMAKULTUR DI PURBALINGGA - Yusak Hartanto Gondo; Hardiyati Hardiyati; Kusumaningdyah Nurul Handayani (Universitas Sebelas Maret Surakarta, 2017)
Abstract: Despite its potentials to be developed as a farming district, Purbalingga faces numerous land reforms and decline of workforce in agriculture field. It also lacks proper agricultural education institution. This design proposal aims to solve the problems. Agriculture Vocational High School, applying Permaculture System in Purbalingga offers four focus programs: agriculture, livestock farming, fishery, and food technology. The school is not only providing education for the students, but also for the local farmers and entrepreneurs of the fiels. The applied permaculture approach asks for five principles (deduced from the fourteen original principles) to be fulfilled: integrated location, biological source, humanly scale, energy cycle, and power-source planning. Keywords: vocational high school, agriculture, permaculture, purbalingga.